ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI KEBANGKRUTAN PADA PT. AGRIFOOD PUTRA SURYA - Situmorang, Dokman Marulitua; Herawati, Mira; Djong, Alexander Mario Retto (Journal Accounting International Mount Hope, 2023)
This study analyzes financial ratios to predict the bankruptcy level of PT Agrifood Putra Suryafrom 2018 to 2022 and the accuracy of the Altman Z-score method in calculating bankruptcypredictions for company purposes. The research uses primary data in the form of companyfinancial reports from 2018 to 2022 which were obtained directly from PT Agrifood Putra Surya.The type of assessment used is descriptive using quantitative methods to calculate financialratios. Altman Z-score analysis in 2018-2020 PT Agrifood Putra Surya is in the gray area,indicating the company is in a vulnerable position. The company continues to suffer losses dueto weak sales and the Covid-19 pandemic. In circumstances like this, companies face financialproblems that need to be managed well. Meanwhile, in 2021 and 2022, PT. Agrifood Putra Suryais starting to rise and is in a safe area with a high Z-score of 5.48 for 2021. PT Agrifood PutraSurya is still surviving and starting to rise in this dynamic situation.